Effect of a sheared flow on iceberg motion and melting. Issue 24 (27th December 2016) - FitzMaurice, A.; Straneo, F.; Cenedese, C.; Andres, M.
Abstract: Icebergs account for approximately half the freshwater flux into the ocean from the Greenland and Antarctic ice sheets and play a major role in the distribution of meltwater into the ocean. Global climate models distribute this freshwater by parameterizing iceberg motion and melt, but these parameterizations are presently informed by limited observations. Here we present a record of speed and draft for 90 icebergs from Sermilik Fjord, southeastern Greenland, collected in conjunction with wind and ocean velocity data over an 8 month period. It is shown that icebergs subject to strongly sheared flows predominantly move with the vertical average of the ocean currents. If, as typical in iceberg parameterizations, only the surface ocean velocity is taken into account, iceberg speed and basal melt may have errors in excess of 60%. These results emphasize the need for parameterizations to consider ocean properties over the entire iceberg draft. Key Points: A novel record of 90 icebergs in Sermilik Fjord indicates that icebergs are subject to strongly sheared flows over the range of their draft Icebergs are able to move fastest when their drafts are around the depth of the interface between the upper and lower fjord layers Ocean shear has a leading order impact on iceberg velocity and melt rate and should be incorporated into models of iceberg motion and melt